2015
DOI: 10.1103/physrevlett.114.174301
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the Dynamic Yield Point of Shocked Aluminum Using Elastodynamic Simulations of Dislocation Dynamics

Abstract: When a metal is subjected to extremely rapid compression, a shock wave is launched that generates dislocations as it propagates. The shock wave evolves into a characteristic two-wave structure, with an elastic wave preceding a plastic front. It has been known for more than six decades that the amplitude of the elastic wave decays the further it travels into the metal: this is known as "the decay of the elastic precursor". The amplitude of the elastic precursor is a dynamic yield point because it marks the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…This numerical work improves existing (quasi-static) discrete dislocation plasticity simulations wherein spurious dislocations can appear ahead of a shock wave front because stress fields are transmitted instantaneously, violating the causality principle. Application of the method to a study of precursor decay in aluminum [26] demonstrated reasonable agreement of stress relaxation in shock fronts at various strain rates, considering only effects of nucleation of new dislocations (i.e., no pre-existing defects) in a linear elastic medium. It was noted how cumulative effects of shielding dislocations exceed those of anti-shielding dislocations, and defect morphologies reminiscent of Smith-Hornbogen interfaces [29][30][31][32] were predicted by the simulations.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…This numerical work improves existing (quasi-static) discrete dislocation plasticity simulations wherein spurious dislocations can appear ahead of a shock wave front because stress fields are transmitted instantaneously, violating the causality principle. Application of the method to a study of precursor decay in aluminum [26] demonstrated reasonable agreement of stress relaxation in shock fronts at various strain rates, considering only effects of nucleation of new dislocations (i.e., no pre-existing defects) in a linear elastic medium. It was noted how cumulative effects of shielding dislocations exceed those of anti-shielding dislocations, and defect morphologies reminiscent of Smith-Hornbogen interfaces [29][30][31][32] were predicted by the simulations.…”
Section: Introductionmentioning
confidence: 87%
“…Given a constitutive model for the stress dependence of dislocation velocity υ D , values of initial dislocation density, b, and θ, and linear elastic properties G=G 0 , c l =c l0 , the differential equation (2.9) [or even more simply (2.7) with (2.8)] can be integrated numerically to predict precursor decay, i.e., stress P at the front versus time t or propagation distance X. The recent numerical study of [26] invokes dynamic discrete dislocation mechanics and analytical expressions from [16,22,24,43] to compute effects of injected and subsequently moving and interacting dislocations, with potentially complex morphologies, on precursor decay.…”
Section: Discrete Dislocation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It is the material yield stress under compression and is also called the elastic shock precursor. Several researchers studied the precursor decay phenomenon in a variety of metallic materials using experiments [1,2] and the molecular dynamics approach [3,4]. Its decay along the shock direction is linked to the evolution of defects such as interfaces, stacking faults, dislocations, twins, vacancies, and interstitials in the shock fronts and to the rise of plasticity in materials.…”
Section: Introductionmentioning
confidence: 99%